White Light-Emitting Flexible Displays with Quantum-Dot Film and Greenish-Blue Organic Light-Emitting Diodes - Young Woo Kim; Seojin Kim; Chaeyeong Lee; Joo Hyun Jeong; Yun Hyeok Jeong; Yuhwa Bak; Seo Hyeon Kim; Sung Jin Park; Ko Eun Ham; Doeun Lee; Junpyo Song; Youngjin Song; et al. (Micromachines)
White organic light-emitting diodes (OLEDs) represent a significant technology in the display industry for the achievement of full color. However, sophisticated technologies are required for white light emission. In this paper, we developed a simple white light-emitting display device using a quantum-dot (QD) film and a greenish-blue OLED. The resulting QD-OLED produced a high-purity white color with a color temperature of 6000 K (CIEx,y = 0.32, 0.34) and achieved a maximum brightness of 14,638 cd/m2 at 7 V. This paper reports the fabrication of a white light-emitting QD-OLED with a straightforward structure and technology suitable for flexible displays.